Stress Unseen: The Role of Social Connectedness on Digital Wellbeing for Students and Professionals - Utami, Rahayu Hardianti; Kurniawan, Rizal; Guspa, Anindra (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
The rapid development of technology is making it faster and more accessible for people worldwide to communicate and socialize. However, exposure to and use of online social media can harm wellbeing and psychosocial development, including mental health. This study investigates the relationship between perceived stress and digital wellbeing with social connectedness as a mediator variable. The research participants were recruited by convenience sampling, including 242 students and 100 workers. The regression analysis shows that the study's result implies that stress as a determinant of mental health has a mixed impact on overall digital wellbeing based on an individual's social connectedness. The findings of this study indicate potential long-term benefits or drawbacks in the debate regarding the use of digital media and technology in stressful situations for active users of digital media and technology, particularly among students.